Value of electrocardiograms ordered by junior medical officers in the emergency department. Issue 1 (27th January 2016) - Sabbagh, C.; Khazzaka, A.; Rizkallah, J.; El Kary, N.; Chaddad, M.; El Rassy, E.
Abstract: The diagnostic rationale for patients with chest pain requires an electrocardiogram (ECG) often limited by low pretest values and widely variable post‐test values. We assess the value of ECG ordered and interpreted by internal medicine junior medical officers in our emergency department (ED). Participants enrolled in this study included patients who presented to the ED for chest pain between June and October 2014. Seventeen leads ECG were performed systematically when an ECG was judged required by the medical officer in charge and interpreted by a blinded medical officer and ED attending. Ultrasensitive troponin T (usTrop T) and creatinine were also withdrawn. Junior medical officers ordered ECG more commonly for atypical chest pain (57 vs 43%, P  = 0.049). Univariate and multivariate analysis did not demonstrate a statistically discordant diagnosis between the medical officer and the attending throughout the study period and between the different rotations. We demonstrated 97% sensitivity, 95% specificity, 92% positive predictive value, 98% negative predictive value and 96% accuracy. Our junior medical officers demonstrated an overall high proficiency in the clinical and bedside setting. This finding reinforces our ECG education in the undergraduate curriculum, highlights the importance of the intensive recapitulation sessions undergone at the beginning of the training programme and our daily internal medicine staff discussions rarely performed in other EDs as reported with our experience.